Survey Kesadaran dan Akses Informasi Tentang Kesehatan Mental Pada Remaja di Wilayah Kerja UPTD Puskesmas III Denpasar Utara - Kadek Sri Ariyanti; Putu Arik Herliawati; Triyana Puspa Dewi; I Nyoman Dharma Wisnawa (Universitas Pahlawan Tuanku Tambusai, 2025)
Mental health is a problem that has not been fully resolved, both at the global and national levels. More than 19 million people aged over 15 years experience mental emotional disorders. Various mental health problems are reported to appear in adolescence such as depression, anxiety, low self-esteem and hopelessness. Accessibility of mental health information is very important to increase adolescent knowledge and foster positive attitudes towards adolescent mental health. This research aims to determine the picture of awareness and access to information about mental health among teenagers in the UPTD Puskesmas III Work Area, North Denpasar. The research method used is descriptive. The survey was conducted on teenage respondents aged 12-19 years in Denpasar City. The number of samples in this study was 65 people taken randomly from several middle and high schools in the UPTD Puskesmas III Work Area, North Denpasar. The instrument used in this research was a questionnaire presented online. Data analysis was carried out using a univariate method which displays the frequency distribution of each variable using SPSS. The research results showed that the majority of teenagers stated that mental health was important to understand (83.1%), the majority of teenagers had accessed mental health information (83.1%), most often via the internet/Google (56.9%). The thing that makes it easier to access adolescent health information is social media (60%) while the thing that hinders access to adolescent mental health information is the lack of access to adolescent mental health information (38.5%).